2020
DOI: 10.4103/wjnm.wjnm_24_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 68Ga-DOTA-NaI3-Octreotide/tyr3-octreotate positron emission tomography/computed tomography and contrast-enhanced computed tomography in localization of tumors in multiple endocrine neoplasia 1 syndrome

Abstract: The optimum imaging modality for the screening of multiple endocrine neoplasia type 1 (MEN1)-associated tumors is not well established. Here, we compare the performance of contrast-enhanced CT (CECT) versus 68 Ga DOTA-NOC/TATE PET/CT in MEN1 patients. The retrospective case record study is conducted at a tertiary health-care center. Thirty-four patients, who have undergone both CECT and 68 Ga DOTA-NOC/ TATE PET, were included in the analysis. CECT had higher per-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
(47 reference statements)
0
6
0
1
Order By: Relevance
“…In the most recent clinical practice MEN1 guideline it is suggested that local expertise and availability may determine the surveillance program. 1 At present, nine studies have reported data on the use of SRI PET/CT in the surveillance of MEN1 patients [18][19][20][21][22][23][24][25][26] but only four explicitly investigated the role of SRI PET in relation to change in treatment. Three supported the use of SRI PET since the PET signal had a significant impact on the decision to do primary pancreatic surgery 19,23,24 and one did not 18 since PET only led to a change in treatment in 1/33.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the most recent clinical practice MEN1 guideline it is suggested that local expertise and availability may determine the surveillance program. 1 At present, nine studies have reported data on the use of SRI PET/CT in the surveillance of MEN1 patients [18][19][20][21][22][23][24][25][26] but only four explicitly investigated the role of SRI PET in relation to change in treatment. Three supported the use of SRI PET since the PET signal had a significant impact on the decision to do primary pancreatic surgery 19,23,24 and one did not 18 since PET only led to a change in treatment in 1/33.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, nine studies investigating the use of SRI PET/CT in MEN1 patients, have been published with conflicting results. [18][19][20][21][22][23][24][25][26] The aim of this retrospective study was to investigate the impact of SRI PET in a cohort of MEN1 patients. Primary outcomes were: Inclusion criteria were patients with a MEN1 diagnosis based on the identification of a pathogenic or probably pathogenic MEN1 gene variant classified according to the guidelines from The American College of Medical Genetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 68 Ga-Ga-DOTA-TOC detected 15 of 25 subcentimetric duodenopancreatic lesions that were not visualised by CECT. Finally, Patil et al, have reported their experience from a retrospective analysis of 34 MEN1 patients evaluated by either  68 Ga-Ga-DOTA-TATE or NOC and CT (16). PET was found to detect more lesions than CT (per-lesion: 74.1% vs 63.7%, p=0.23 and per-patient: 89.2% vs 71.4%, p=0.09), with a PPV of 100% for both modalities.…”
Section: Discussionmentioning
confidence: 99%
“…SSTR PET has progressively replaced somatostatin receptor scintigraphy (SRS) due to its many advantages (i.e., greater image resolution, shorter imaging times, lower radiation exposure, cheaper costs in properly equipped departments). At present, the value of SSTR PET/CT in MEN1-associated NETs has been evaluated in six studies with very promising results in terms of lesion detection and impact on patient management (12)(13)(14)(15)(16)(17)(18). Overall, SSTR PET often detects more primary NETs (except thymic carcinoids) and metastases than morphological imaging, with very few false positives.…”
Section: Introductionmentioning
confidence: 99%